Culture of Control versus the Culture of Resistance in the Case of Control of Forest - Maring, Prudensius (UI Scholars Hub, 2015)
The implementation of rights, policy, forest official, and repressive approach by the government shows that the culture of control is applied at forest tenure. This research showed that the application of cultural control by the Government clashed with the interests of local wisdom and socio-economic communities around the forest. The local community have developed strategies and tactics to resist the Government through controlling the land, determining the types of plant, and by implementing community-based forest management system. These resistance strategies and tactics is the manifestation of the socio-economic conditions which are integrated in the community culture. Through the perspective of power (Foucault) and resistance (Scott), this research shows the urgency to put culture and behavior as the focus of an analysis particularly in the midst of a strong influential political ecology perspective. The focus on culture and behavior means that an analysis on controlling culture is not only to discuss the strategy of fulfilling the formal rights of the government, but also to discuss the arrogant, repressive and proud behavior of the government of its authority and power. Equally, the analysis of the culture of resistance does not only discuss the strategy to get the formal rights of the community, but also deliberate on the behavior of the community to implement their strategy quietly, secretly, and • while avoiding the forest staff.